The Arabidopsis thaliana Cyclic-Nucleotide-Dependent Response – a Quantitative Proteomic and Phosphoproteomic Analysis - Alqurashi, May M. (2013)
Protein phosphorylation governs many regulatory pathways and an increasing number of kinases, proteins that transfer phosphate groups, are in turn activated by cyclic nucleotides. One of the cyclic nucleotides, cyclic adenosine monophosphate (cAMP), has been shown to be a second messenger in abiotic and biotic stress responses. However, little is known about the precise role of cAMP in plants and in the down-stream activation of kinases, and hence cAMP-dependent phosphorylation. To increase our understanding of the role of cAMP, proteomic and phosphoproteomic profiles of Arabidopsis thaliana suspension culture cells were analyzed before and after treatment of cells with two different concentrations of 8-Bromo-cAMP (1 µM and 100 nM) and over a time-course of one hour. A comparative quantitative analysis was undertaken using two- dimensional gel electrophoresis and the Delta 2D software (DECODON) followed by protein spot identification by tandem mass spectrometry combined with Mascot and Scaffold. Differentially expressed proteins and regulated phosphoproteins were categorized according to their biological function using bioinformatics tools. The results revealed that the treatment with 1 µM and 100 nM 8-Bromo-cAMP was sufficient to induce specific concentration- and time-dependent changes at the proteome and phosphoproteome levels. In particular, different phosphorylation patterns were observed overtime preferentially affecting proteins in a number of functional categories, notably phosphatases, proteins that remove phosphate groups. This suggests that cAMP both transiently activates and deactivates proteins through specific phosphorylation events and provides new insight into biological mechanisms and functions at the systems level.